System‐level dynamic phasor models of hybrid AC/DC microgrids suitable for real‐time simulation and small signal analysis. Issue 15 (25th May 2018) - Xu, Jin; Wang, Keyou; Li, Guojie; Ji, Weijiang; Jiang, Xiuchen; Zhang, Hua
Abstract : This study develops a system‐level dynamic phasor (DP) model of a hybrid AC/DC microgrid. A new definition of DP, based on the multiple frequency shift transformation, is proposed to extend the models of a variety of AC/DC and DC/DC converters. The comprehensive control system is considered in developing the DP model of microgrid. Furthermore, a computational framework for applying this DP model into system‐level simulation and small signal analysis (SSA) is given. The DP‐based simulation is tested under conditions of environmental disturbances and unbalanced supply voltages. The SSA is performed on the developed DP model to evaluate the voltage stability and harmonic modes of the microgrid. Besides, this DP model shows high potential when implemented in the real‐time simulation with larger scale system.